Plasma etching of SiO2 contact hole using perfluoropropyl vinyl ether and perfluoroisopropyl vinyl ether - You, Sanghyun; Kim, Jun Hyun; Kim, Chang Koo (Korean Journal of Chemical Engineering, 2022)
Perfluoropropyl vinyl ether (PPVE) and perfluoroisopropyl vinyl ether (PIPVE) are used for plasma etching of SiO2 contact holes. When etching is performed on blanket SiO2 samples, the etch rates in the PPVE/Ar plasma are higher than those in the PIPVE/Ar plasma at all bias voltages. In contrast, when hole-pattern (100 nm in diameter) SiO2 samples are etched, the etch rates of the SiO2 hole in the PIPVE/Ar plasma are higher than those of the SiO2 hole in the PPVE/Ar plasma. This can be attributed to excess production of CF3+ ions in PIPVE than in PPVE, and higher contribution of physical sputtering to plasma etching in PIPVE than in PPVE. The angular dependence of the SiO2 etch rates examined using a Faraday cage reveals that the effect of physical sputtering on the SiO2 etching is greater in the PIPVE/Ar plasma than in the PPVE/Ar plasma.
Keywords: Angular Dependence; Contact Hole; PIPVE; Plasma Etching; PPVE